1999
DOI: 10.1017/s0031182098003928
|View full text |Cite
|
Sign up to set email alerts
|

Mini-exon gene sequence polymorphism among Trypanosoma rangeli strains isolated from distinct geographical regions

Abstract: Trypanosoma rangeli can infect humans and the same domestic and wild animals and triatomine vectors infected by T. cruzi in Central and South America. This overlapping distribution complicates the epidemiology of Chagas disease because of the cross-reactivity between T. rangeli and T. cruzi antigens. We have studied T. rangeli strains isolated from different geographical regions using the mini-exon gene as a genetic marker. Two pairs of oligonucleotides directed to this gene were designed in order to detect sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
19

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 28 publications
5
34
0
19
Order By: Relevance
“…Our results are in agreement with previous data based on DNA fingerprinting, RAPD and mini-exon gene sequences analysis that showed that T. rangeli populations from Southern Brazil are distinct from T. rangeli from Colombia, Venezuela and Honduras (Macedo et al 1993, Steindel et al 1994, Grisard et al 1999a, Stevens et al 1999.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our results are in agreement with previous data based on DNA fingerprinting, RAPD and mini-exon gene sequences analysis that showed that T. rangeli populations from Southern Brazil are distinct from T. rangeli from Colombia, Venezuela and Honduras (Macedo et al 1993, Steindel et al 1994, Grisard et al 1999a, Stevens et al 1999.…”
Section: Discussionsupporting
confidence: 94%
“…A weak hybridization with this gene probe was observed in the compression zone of gels (above 1000 Kb) in T. rangeli SC 58, SC 61 and Pepita Gonzales strains, that may represent a small number of gene copies in a larger chromosome. This polymorphism observed among T. rangeli strains is in agreement with early reports from Macedo et al (1993) using DNA fingerprinting, Steindel et al (1994) using isoenzyme electrophoresis and RAPD, and Grisard et al (1999a) using the mini-exon gene sequence analysis.…”
Section: Discussionsupporting
confidence: 91%
“…It is interesting that two groups of T. rangeli were previously described by Vallejo et al (1994) when amplifying the conserved region of minicircle molecules. Polymorphism among strains from distinct geografical origin was also evidenced using the mini-exon primary DNA sequence and low stringency single specific primer PCR (LSSP-PCR) profiles (Grisard et al 1999). Therefore, as different markers are examined the finding of polymorphism among T. rangeli isolates is becoming a common observation.…”
mentioning
confidence: 99%
“…However, current PCR assays used for mixed infection detection show some disadvantages such as the amplification of bands of similar size both in T. cruzi and T. rangeli 27,28 , the amplification of polymorphic fragments 11,19 , and bias to T. cruzi in the case of mixed T. cruzi and T. rangeli infection 9,33,36 . Therefore, it is necessary to develop new techniques as better options to specifically identify each of these parasite species in mixed infections.…”
Section: Introductionmentioning
confidence: 99%